KETIDAKMERATAAN KEKAYAAN: KAJIAN LITERATUR TENTANG IMPLIKASI SOSIAL DAN EKONOMI - Loso Judijanto; Al-Amin (Adiba Aisha Amira, 2024)
Wealth inequality is considered a critical issue that impacts various aspects of people's lives. The research method in this study uses the literature method. The results show that wealth inequality not only creates social injustice but also negatively affects political stability and social cohesion. From an economic perspective, the accumulation of wealth in a handful of individuals or groups can hinder sustainable economic growth by reducing investment levels and widening the economic opportunity gap. Addressing wealth inequality through policies such as progressive tax reform, improved access to education, and social safety net programs are important measures to achieve inclusive and sustainable social welfare and economic prosperity.